The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11249-016-0656-0
|View full text |Cite
|
Sign up to set email alerts
|

Shearing Nanometer-Thick Confined Hydrocarbon Films: Friction and Adhesion

Abstract: We present Molecular Dynamics (MD) friction and adhesion calculations for nanometer-thick confined hydrocarbon films with molecular lengths 20, 100 and 1400 carbon atoms. We study the dependency of the frictional shear stress on the confining pressure and sliding speed. We present results for the pull-off force as a function of the pull-off speed and the sliding speed. Some of the results are analyzed using the simple cobblestone model and good semi-quantitative agreement between the model predictions and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
2
2
1
Order By: Relevance
“…Figure 11 shows that σ 0 increases approximately linearly with logarithmic shear rate for all of the n-alkanes studied, in agreement with previous simulations of atomic fluids at high shear rate [72]. In Figure 11, σ 0 is larger for longer n-alkanes, as observed in previous NEMD simulations of n-alkanes (C 20 -C 100 ) [73]. For short n-alkanes at low shear rate, a negative σ 0 is extrapolated from Figure 8, which was also noted from previous NEMD simulations of atomic fluids [72] and C 16 [67].…”
Section: Accepted Manuscriptsupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 11 shows that σ 0 increases approximately linearly with logarithmic shear rate for all of the n-alkanes studied, in agreement with previous simulations of atomic fluids at high shear rate [72]. In Figure 11, σ 0 is larger for longer n-alkanes, as observed in previous NEMD simulations of n-alkanes (C 20 -C 100 ) [73]. For short n-alkanes at low shear rate, a negative σ 0 is extrapolated from Figure 8, which was also noted from previous NEMD simulations of atomic fluids [72] and C 16 [67].…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Unlike branched alkane films [19], most of the n-alkanes show a finite σ 0 in Figure 11, suggesting some adhesion at the solid-liquid interface [68]. Non-zero values of σ 0 have also been obtained from previous NEMD simulations and experiments of a range of confined fluids [72,67,68,73,24]. Figure 11 shows that σ 0 increases approximately linearly with logarithmic shear rate for all of the n-alkanes studied, in agreement with previous simulations of atomic fluids at high shear rate [72].…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…We note that this study, and that in [2], involve fluid squeeze-out between a curved surface and a nominally flat surface. This differs from our earlier (frictional) studies involving flat surfaces [3][4][5][6].…”
Section: Introductioncontrasting
confidence: 99%
“…In particular, this type of systems have been extensively studied through SFA experiments by Israelachvilli, who, among other things, found that friction at the nano-scale could be correlated with the adhesion hysteresis phenomenon [6]. Furthermore, in order to achieve a fundamental understanding of these processes, efforts have and are still been made from both experimental [7][8][9][10][11][12][13][14][15] as well as theoretical and simulations points of view, such as through Molecular Dynamic Simulations (MDS) [16][17][18][19][20][21][22][23][24][25][26][27][28]. However, a satisfactory explanation of the friction mechanisms involved in this type of systems is still lacking, for example, with respect to the origin of phase transitions evidenced by the SS behavior and the effects of the adhesion hysteresis phenomenon.…”
Section: Introductionmentioning
confidence: 99%